2014
DOI: 10.1158/1055-9965.epi-13-0902
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Primary Malignancies in Patients with Nonmelanoma Skin Cancer in England: A National Record-Linkage Study

Abstract: Background: Conflicting evidence exists about whether people with a history of nonmelanoma skin cancer (NMSC) are at higher risk of subsequent primary malignant cancers than those without.Methods: An all England record-linked hospital and mortality dataset spanning from 1999 to 2011 was used. We constructed two cohorts: one that comprised people with a history of NMSC (502,490 people), and a control cohort that comprised people without. We "followed up" these two cohorts electronically to determine observed an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 33 publications
6
39
0
Order By: Relevance
“…Others have also found higher risks of subsequent cancer after NMSC in younger age groups. [13], [21] Studies of Kaiser Permanente patients reported estimates of relative risk closer to ours, based on 822 patients with in situ or invasive SCC (HR 1.4; 95% CI 1.2, 1.6) [8], and on 3164 patients with BCC (HR 1.2; 95% CI 1.1, 1.4) [9]. Chen studied 165 individuals with SCC, 513 with BCC, 60 with both and 31 with unknown subtype from the volunteer-based CLUE II cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also found higher risks of subsequent cancer after NMSC in younger age groups. [13], [21] Studies of Kaiser Permanente patients reported estimates of relative risk closer to ours, based on 822 patients with in situ or invasive SCC (HR 1.4; 95% CI 1.2, 1.6) [8], and on 3164 patients with BCC (HR 1.2; 95% CI 1.1, 1.4) [9]. Chen studied 165 individuals with SCC, 513 with BCC, 60 with both and 31 with unknown subtype from the volunteer-based CLUE II cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although KC has a low mortality rate of 1/100,000 [1,2], several previous studies have suggested a positive association between the history of KC and the risk of subsequent second primary cancers (SPCs) in other organs [610]. A meta-analysis reported that KC was associated with about a 10% increased risk of SPCs [7].…”
Section: Introductionmentioning
confidence: 99%
“…13 Inherited predisposition may be a contributory factor 4 as this association is stronger in those with early age-of-onset KC. 1, 2 A positive family cancer history is associated with increased cancer risk. 5 However, skin cancer is usually ignored when investigating family cancer history.…”
mentioning
confidence: 99%